Pengaruh Pola Makan Terhadap Status Gizi Anak Sekolah Dasar - Hasrul Hasrul; Hamzah Hamzah; Aslinda Hafid (Jurnal Keperawatan Muhammadiyah, 2020)
Nutritional status is a state of the body as a result of food consumption and use  nutritional substances. Almaizer, 2006 in(NS Mustika, 2015).  Nutrition problems in elementary school children are still quite high at this time. Based on the results of Basic Health Research (Riskesdas) year 2018 obtained nutritional status of children 5-12 years according to body mass index in Indonesia, i.e. prevalence lean is 9,3, consists of 2,5% very lean dan 6,8% lean. Consumption of good food but the condition of a sick or infectious disease can cause the child to experience poor nutritional status as well (Oktafiani, 2016). Nutrition improvement is needed starting from pregnancy, baby and toddler, preschool, elementary school age children, a teenager dan adult, until old age. Elementary school age children is a strategic target in improvement community nutrition because of in period child function brain organ begin to form perfection so that the development of intelligence is quite rapid (Oktafiani, 2016). Imbalance between intake and nutritional adequacy will cause nutritional problems, that's good nutritional problems more as well as malnutrition (Septrianty, 2015).